1995
DOI: 10.1111/j.1651-2227.1995.tb13649.x
|View full text |Cite
|
Sign up to set email alerts
|

Aminophylline versus caffeine citrate for apnea and bradycardia prophylaxis in premature neonates

Abstract: We investigated the efficacy and adverse effects of aminophylline and caffeine citrate in 180 premature neonates for 10 days and nights. Aminophylline (n = 98) and caffeine citrate (n = 82) were equally effective in preventing apnea and bradycardia. The caffeine citrate group had a lower median heart rate on day 3, fewer neonates with tachycardia and a smaller amount of gastric aspirate on day 7. The need for mononasal continuous positive airway pressure and respirator therapy was similar in both groups. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…[109,110] Significant adverse effects reported by these studies consist of increased tachycardia and gastrointestinal disturbances with theophylline. [105][106][107][108] Most authors prefer caffeine due to its ease of administration (once daily) and wider margin of tolerability, with fewer cardiovascular adverse effects.…”
Section: Comparative Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[109,110] Significant adverse effects reported by these studies consist of increased tachycardia and gastrointestinal disturbances with theophylline. [105][106][107][108] Most authors prefer caffeine due to its ease of administration (once daily) and wider margin of tolerability, with fewer cardiovascular adverse effects.…”
Section: Comparative Trialsmentioning
confidence: 99%
“…There are a number of comparative studies of aminophylline or theophylline, and caffeine [105][106][107][108] or doxapram [109,110] (table III). Studies comparing theophylline and caffeine have found them to be of comparable efficacy, although the administration regimens and routes of administration vary widely, especially for theophylline.…”
Section: Comparative Trialsmentioning
confidence: 99%
“…Our randomized study was carried out in two centres, but the policies regarding weaning and extubation were very similar. Although in one institution theophylline or caeine was used and in the other aminophylline, the two medications have been shown to have similar ecacy, at least in treating infants with apnoea [9]. Two dierent forms of CPAP were used, but although it has been claimed that the binasal system has superior function [8], this has been disputed [10].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a study found similar efficacy of aminophylline and caffeine in preventing AOP, although their aminophylline dose was lower than that of our study. 8 Aminophylline is from the same family of drugs as caffeine and has a similar mechanism of action, i.e., affecting the same adenosine receptors (adenosine A 1 , A 2A and A 3 receptors). 9,10 Aminophylline is metabolized by the body into several active forms, but due to incomplete liver development in premature infants, several metabolites from aminophylline cannot be activated.…”
Section: Discussionmentioning
confidence: 99%